2022
DOI: 10.3390/diagnostics12071695
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Associated Urinary Tract Infection in Intensive Care Unit Patients at a Tertiary Care Hospital, Hail, Kingdom of Saudi Arabia

Abstract: Catheter-associated urinary tract infections (CAUTIs) are some of the most common hospital-acquired infections (HAIs). Prolonged hospitalization, invasive devices such as catheters, and irrational use of antimicrobial agents are believed to be the major causes of high rates of HAIs. Infections such as pyelonephritis, urethritis, cystitis, and prostatitis are the main concerns in catheterized ICU patients. In these cases, Gram-negative bacteria are the most common bacteria. The present study was undertaken to d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
(29 reference statements)
4
8
2
Order By: Relevance
“…This variation in clinical types might be due to the differences in the ICU precaution measures and patient population. The most common bacterial isolates reported from our study were K. pneumoniae (39, 24%), followed by A. baumannii (35,21.5%) and P. aeruginosa (25, 15.3%); other authors reported similar findings. 23 In another study by Agarwal et al, A. baumannii was the most common isolate, followed by P. aeruginosa in VAP patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This variation in clinical types might be due to the differences in the ICU precaution measures and patient population. The most common bacterial isolates reported from our study were K. pneumoniae (39, 24%), followed by A. baumannii (35,21.5%) and P. aeruginosa (25, 15.3%); other authors reported similar findings. 23 In another study by Agarwal et al, A. baumannii was the most common isolate, followed by P. aeruginosa in VAP patients.…”
Section: Discussionsupporting
confidence: 81%
“…These MDR pathogens are increasing the burden on the healthcare systems due to nosocomial infections in the ICU settings. [34][35][36] Our study showed that P. aeruginosa and A. baumannii produced three types of beta-lactamases, including MBL, ESBL, and AmpC. In contrast, K. pneumoniae isolates did not produce MBL.…”
mentioning
confidence: 69%
“…Gram negative bacteria (86%) specifically Acinto bacter spp (37%), klebsiella spp (16%), E-coli (11%) and Proteus spp (11%) were the main infectious agent in the study which in line with South, Ethiopian Study [14], Saudi Arabia [15], Ugandan [21] Mohammed Saber’s[1],, Indian[22-24], Fiji[25] and Romanian[26] ICU studies. The most dominant bacteria species in this study; Acinetobacter is commonly originated from water supplies of hospitals and contaminated materials [21].…”
Section: Discussionsupporting
confidence: 72%
“…An overall prevalence of Hospital acquired Urinary Tract infection in the two Hospital ICUs was 91 (23.3%) 95% CI ;(19.4-27.6%) and about 95.6% were associated with urinary catheterization under possibly assessed journals the study finding is the first prevalence report in our country which is particular to ICU. This prevalence of HAUTIs in the study area is much higher than findings of Mohd Saleem et al 6.4% [15], a study done in Italy 2.7% [3], 6.5% of Canadian survey [9], Oumer et al16.8% [14]…”
Section: Discussionmentioning
confidence: 51%
“…Catheter-associated urinary tract infections (CAUTIs) are among the most frequent hospital-acquired infections. There were around eleven publications on CAUTIs [45,47,48,54,56,57,61,62,66,67,74]. CAUTIs are the most common nosocomial infections in KSA, where they account for 7% [54], 20% [61] 22% [66], 24.4% [45], 28.5% [57], and 42% [48] of hospitalacquired infections.…”
Section: Catheter-associated Utismentioning
confidence: 99%